2020
DOI: 10.1002/prca.202000011
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Microbiome Shifts in Response to Periodontal Treatment Outcome

Abstract: Purpose Periodontitis is linked to a localized dysbiotic microbial shift. This trending may often not be evident due to deep taxonomic changes of low abundance organisms and lack of consideration of variations in the treatment response. By using next generation sequencing this study aims to evaluate the salivary microbiome dynamics of periodontal treatment and the implication of treatment outcome Experimental Design Patients with generalized aggressive periodontitis are treated non‐surgically and followed up f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 48 publications
1
30
0
Order By: Relevance
“…Although there are some differences in the classification of the core or predominant oral OTUs between the current and other studies 1,3 , the majority of the species were identified as the core oral OTUs across the studies. Since low-abundance rather than highly abundant OTUs may contribute more to the difference in oral bacterial communities 42,43 , detailed analysis of low-abundance OTUs would be important in future research. O. sinus and S. moorei were previously classified as core OTUs common to the salivary and tongue microbiomes 3 , but in our present study were identified as tongue-specific.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are some differences in the classification of the core or predominant oral OTUs between the current and other studies 1,3 , the majority of the species were identified as the core oral OTUs across the studies. Since low-abundance rather than highly abundant OTUs may contribute more to the difference in oral bacterial communities 42,43 , detailed analysis of low-abundance OTUs would be important in future research. O. sinus and S. moorei were previously classified as core OTUs common to the salivary and tongue microbiomes 3 , but in our present study were identified as tongue-specific.…”
Section: Discussionmentioning
confidence: 99%
“…Deep sequencing of oral samples collected from chronic periodontitis patients demonstrated decreases in the relative abundance of subgingival plaque-specific bacteria in the salivary microbiota following periodontal therapy having significant associations with clinical improvements [101]. Next-generation sequencing was used to determine the non-surgical treatment effects on the saliva microbiome of generalized aggressive periodontitis patients [102]. Clinical improvements were not paralleled by relative abundance changes on the phylum, genus or species level, or diversity indices indicating a resilience of the salivary microbiome to treatment in this category of periodontitis patients.…”
Section: Advances In Dna Sequencing: Next-generation Sequencing For Mmentioning
confidence: 99%
“…Clinical improvements were not paralleled by relative abundance changes on the phylum, genus or species level, or diversity indices indicating a resilience of the salivary microbiome to treatment in this category of periodontitis patients. Interestingly, that study attributed the observed limited microbiome shifts in patients with poor treatment outcomes to a potential emergence or inefficient elimination of virulent species, or to a failure of establishment of commensal species following treatment [102]. The subgingival microbial profile of wellmaintained periodontitis patients (N=14) having no evidence of clinical inflammation and progress of periodontitis was compared with healthy subjects (N=21) by sequencing the V3-V4 region of the 16S rDNA [103].…”
Section: Advances In Dna Sequencing: Next-generation Sequencing For Mmentioning
confidence: 99%
“…It has been shown that a decreased alpha diversity, as well as alterations in certain taxa such as opportunistic Gammaproteobacteria or pathogenic families Enterobacteriaceae and Enterococcaceae , among others, are associated with autoimmune and metabolic disorders, cancer and immunodeficiency states 30 . Microbial indicators have also been described in relation to treatment response in the case of aggressive periodontitis 31 , emphasizing its importance to predict therapeutic outcome, as well as to design preventive, diagnostic and prognostic tools. Therefore, the objective of this study is to evaluate the impact of the selected hypervariable regions on the statistical differentiation of soil samples collected along a pedogenic gradient 26 and saliva samples from healthy individuals with different oral types 28 , 32 , 33 .…”
Section: Introductionmentioning
confidence: 99%